Cognitive load and live coding: a comparison with improvisation using traditional instruments. Issue 2 (2nd July 2016) - Sayer, Tim
ABSTRACT: This paper explores the claim that live coding is a 'real-time' improvisatory activity by examining the difference in the temporal frame used by this and traditional instrumental improvisation, for the creation of novel musical expression. It posits the notion that because live coding requires less complex motor skills than instrumental improvisation, it may be less susceptible to certain types of mechanical modes of musical expression which inhibit musical novelty. This hypothesis is developed to include the concept of goal states, models of memory and cognitive load, as a means of mapping this territory and to provide an understanding of the various perceptual domains with which a coder engages during a live extemporised performance. This work will engage in a comparative discourse relating live coding to instrumental improvisation, as a point of departure for the understanding of cognitive functioning in this rapidly developing performance paradigm.